Long non-coding RNA NEAT1 promotes angiogenesis in hepatoma carcinoma via the miR-125a-5p/VEGF pathway - Guo Jingyun; Yuan Qi; Fang Yuan; Liao Jinmao; Zhang Zheng (Open Life Sciences, 2022)
The study’s purpose was to investigate the biological function of long non-coding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) in hepatoma carcinoma (HCC). HCC tissues and cells exhibited increased levels of NEAT1 and decreased levels of miR-125a-5p. Reduction in the expression of NEAT suppressed HepG2 cell proliferation and increased apoptosis. This was accompanied by suppression of the AKT/mTOR and ERK pathways, while the opposite was observed for miR-125a-5p. Angiogenesis assay results indicated that NEAT was proangiogenic. A dual-luciferase reporter assay indicated that NEAT1 was bound to miR-125a-5p and miR-125a-5p was bound to vascular endothelial growth factor (VEGF). The proangiogenic effects of NEAT and its stimulation of AKT/mTOR and ERK were reversed by miR-125a-5p. The anti-angiogenic effects of miR-125a-5p and its inhibitory effect on AKT/mTOR and ERK pathways were reversed by co-incubation with VEGF. The conclusion was that NEAT1 enhances angiogenesis in HCC by VEGF via a competing endogenous RNA (ceRNA) of miR-125a-5p that regulates AKT/mTOR and ERK pathways.